التظلم الضريبي في التشريع الجزائري - ريان شرياف; خولة مباركي (My University, 2022)
Summary: Recently, the financial sector has been modernized and modernized for all public administrations. It has attached great importance to the tax sector in line with constitutional reform and the requirements of modernity, its affiliates and digitization, which has become imperative, more transparent, and has touched on two aspects of tax reform: The first aspect was the restructuring of the General Directorate of Speculators and Offshore Interests and the simplification of the foundations and tax vessels, both in terms of taxation and collection for greater clarity. The second aspect was the modernization of the fiscal measures to achieve the legitimacy of taxation and collection Flexibility, compassion and psychological satisfaction of the citizen and motivation to contribute to the financing of public costs in a gesture that makes the taxpayer in the position of the officers responsible for implementing it, Giving more flexibility, transparency and the role of a batterer's agents thanks to the enquiry, publication and codification of information and tax procedures would alleviate conflict and controversy and establishes the legal rule that there is no excuse for ignorance of the law. .................................................. ملخص : بادرة وازرة المالية في الآونة الأخيرة إلى تحديث و عصرنة قطاع المالية لكافة المديريات العامة . و قد أولت أهمية كبرى لقطاع الضريبة تماشيا مع الإصلاح الدستوري و متطلبات العصرنة ،التابعة لها و الرقمنة التي أصبحت حتمية، و إضفاء طابع الشفافية أكثر، و قد مس الإصلاح الضريبي جانبين: الجانب الأول تمثل في إعادة هيكلة المديرية العامة لمضارئب و المصالح الخارجية التابعة لها و تبسيط الأسس و الأوعية الضريبية سواء من ناحية فرض الضريبة أو تحصيلها لمزيد من الوضوح والجانب الثاني تمثل في تحديث الإجارءات الجبائية لتحقيق شرعية فرض الضريبة و تحصيلها ،و المرونة و إستعطاف و إستحسان نفسية المواطن و تحفيزه على المساهمة في تمويل التكاليف العمومية في بادرة تجعل المكلف بالضريبة في مقام أعوان الضارئب المكلفين بتنفيذها، ذلك أن إضفاء المزيد من المرونة والشفافية و قيام أعوان الضارئب مقام المواطن بفضل استعلام و نشر و تدوين المعلومات و الإجراءات الضريبية من شأنه تخفيف حدة التنازع و الجدل، و يؤسس للقاعدة القانونية التي تقضي بأنه لا عذر بجهل القانون.